Saving Our Children From Poverty : What the United States Can Learn From France - Bergmann, Barbara R. (Book collections on Project MUSE., 1996)
Saving Our Children From Poverty compares the American aversion to national assistance programs with the French commitment to child well-being. Americans' lack of faith in the federal government, a growing resistance to taxation, and a belief that financial support encourages irresponsibility have weakened support for U.S. welfare programs. Saving Our Children From Poverty illustrates what a nation no wealthier than ours can realistically accomplish and concludes with a viable blueprint for successfully applying aspects of France's system to the United States. Its insights may help us to realize the importance of helping America's most undeserving poor.